Factors affecting vocational training activities for unemployed workers laid off by businesses in Ho Chi Minh City, Vietnam - Khanh, Pham Ngoc; Hoa, Le Thi Kim; Cuong, Ngo Anh (Edelweiss Applied Science and Technology, 2025)
The objective of the article is to determine and measure the influence of factors on vocational training activities for unemployed workers laid off by businesses in Ho Chi Minh City. Based on data collected from 340 unemployed workers fired by businesses, processed with SPSS 27.0 software, including assessing the reliability of the scales using Cronbach's Alpha coefficient; EFA exploratory factor analysis with Bartlett and KMO tests; and regression analysis of factors and their influence on vocational training activities using the F test and significance level to test the hypotheses. Research results show that there are five factors affecting vocational training activities for unemployed workers: (i) State support policies; (ii) Labor market; (iii) Factors belonging to the business; (iv) Factors belonging to vocational education institutions; and (v) Training program content. On that basis, the article proposes management implications to improve the effectiveness of vocational training activities for unemployed workers laid off by businesses.